CORAL COMMUNITIES, ZONATION AND PALEOECOLOGY OF AN UPPER JURASSIC REEF COMPLEX (ELLIPSACTINIA LIMESTONES, CENTRAL APENNINES, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
This work describes and analyzes an original collection of fossil corals from the Ellipsactinia Limestones (Kimmeridgian-Tithonian), exposed in the Marsica area (central Apennines, Italy), focusing on taxonomy and paleoecology. 43 species grouped into 32 genera, 16 families and 9 suborders were identified. Astreoidogyra giadae nov. gen. nov. sp. (Rhipidogyridae) and Clausastrea eliasovae nov. sp. (Montlivaltiidae) are new taxa. Corals occur from the back reef to the reef crest, showing a marked zonation, expressed by a variation of coral cover and type, although the reef front and slope facies could not be sampled. The back reef is characterised by scattered medium-to-small colonies, with a relative high variety of colony shape, corallite arrangement types and high taxonomic diversity. Stylosmilia, Calamophylliopsis, Intersmilia, Pleurophyllia, Bracthelia, Heliocoenia, Ogilvinella occur here among others. The inner reef flat records the highest coral cover, with large robust branching, such as “Pseudocoenia”, Heliocoenia, Calamophylliopsis, and large dome-shaped meandroid, such as Psammogyra, Pruvostrastraea, Eugyriopsis) colonies. Within the external reef flat and the reef crest the coral cover is low and the stromatoporoid-bearing mounds dominate on the isolated coral bioconstructions. Controlling factors as bathymetry, hydrodynamic disturbances, abrasive currents, background sedimentation and morphological irregularities of the depositional profile are considered to explain the observed coral zonation. High diversity and low dominance indices are interpreted to result from reef complex heterogeneity, which should have influenced the formation of different ecological niches and consequently the proliferation of a greater number of taxa in a relatively small area.